Effect of using supplementation mineral or organic selenium with vitamin E as antioxidants in the flushing diet on the fertility of ewes - SAFDAR, AMIR HOSSEIN ASGARI; MAGHAMI, SAEED POUR MAHDI GHAEM; NEJAD, AREFE ESALAT (The Indian Journal of Animal Sciences, 2021)
In this study, 44 Afshari ewes were investigated that were 1–4 years old with a mean weight of 54–51 kg, with a physical score of approximately three in four experimental groups. Ewes were randomly assigned into four experimental groups including Group A Control (base diet recipient), Group B (Flushing), Group C (Flushing + Vitamin E Supplement + Organic Selenium), and Group D (Flushing + Vitamin E Supplement + Mineral Selenium). Blood sampling was carried out at different intervals namely beginning of the course, 24 h prior to CIDR, 24 h after CIDR (estrus), and 21 days after mating (at the time of embryonic implantation). Blood serum hormones (estrogen, progesterone, and insulin) were measured. The results of this study showed improvement in reproductive efficiency, especially the percentage of lambing, the fertility rate in Afshari breed. The use of organic selenium supplement with vitamin E and mineral selenium with vitamin E in the flushing diet before mating increased the reproductive performance of Afshari breed sheep by increasing the number of reproductive hormones (estrogen, progesterone, and insulin). C and A treatment had the highest and lowest lambs, respectively with 14 and 10 progenies. The highest birth weight of lambs was related to C treatment with an average of 4.49 kg. The use of two Flashing factors and vitamin E and organic selenium supplementation significantly increased the estrus and fertility, and significantly reduce the non-pregnant ewes by controlling oxidative conditions and increasing sex hormones.